KONTRIBUSI AL-QUR’AN DALAM MENGEMBANGKAN PEMBELAJARAN AKTIF (ACTIVE LEARNING) DI LEMBAGA PENDIDKAN - Karman Karman (al-Iltizam: Jurnal Pendidikan Agama Islam, 2018)
Abstract: The Qur'an as a "silent book" when invited to dialogue produces important principles in learning, such as the principle of the use of the drill method. The drill method in learning has been understood as a supporter of behavioristic theory. This paper aims to explain the contribution of the Qur'an in the development of active learning, especially the drill method. The method used to analyze this paper is a thematic interpretation with a multidisciplinary approach. The results of the analysis show that the drill method offered by the Qur'an is oriented towards students. This learning supports the humanistic and constructivist theories developed in educational institutions. The Qur'an can be said to have contributed theoretically and practically to inquiry learning development (group work), discovery, and self-direct-learning (independent learning). The drill method can build students' creativity and innovation. Al-Qur‟an sebagai “kitab bisu” ketika diajak berdialog menghasilkan prinsipprinsip penting dalam pembelajaran, seperti prinsip pengguna-an metode drill. Metode drill dalam pembelajaran selama ini dipahami sebagai pendukung teori behavioristik. Tulisan ini bertujuan menjelas-kan konribusi al-Qur‟an dalam pengembangan pembelajaan aktif, terutama metode drill. Metode yang digunakan untuk menganalisis tulisan ini tafsir tematik dengan pendekatan multidisipliner. Hasil analisis menunjukkan metode drill yang ditawarkan alQur‟an ber-orientasi pada peserta didik. Pembelajaran ini mendukung teori huma-nistik dan konstruktivistik yang dikembangkan di lembaga pendidikan. Al-Qur‟an dapat dikatakan telah berkontribusi secara teoretis dan praktis bagi pengembangan belajar inquiri (kerja keompok), discovery (penemuan), dan self-direct-learning (belajar mandiri). Metode drill dapat membangun kreativitas dan inovasi peserta didik. Keywords: strategi pembelajaran, konstruktivistik, inquiry, discovery.